PENGARUH PEMBERIAN BORAKS DENGAN DOSIS BERTINGKAT TERHADAP PERUBAHAN MAKROSKOPIS DAN MIKROKSKOPIS GINJAL TIKUS WISTAR SELAMA 4 MINGGU DILANJUTKAN 2 MINGGU TANPA PAPARAN BORAKS - Hakim Alhaady Juhana; Intarniati Nur Rohmah (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Borax or sodium tetraborate decahydrate is a mineral with low toxicity. Borax is generally used in various products such as the product insecticides, fungicides, herbicides, and borax can also be dissolved in water and used to clean gold and silver . However now many are using borax as a food preservative,it is contrary to the minister of health regulations. Borax contained in foods with excessive doses can cause poisoning. However,to date research on the influence of borax in oral histopathological kidney remains unclear.Objective: This study aimed to verify the effect of graded doses of borax orally for 4 weeks followed 2 weeks to changes in macroscopic and microscopic picture of Wistar rat kidney.Methods : The research laboratory with an experimental post -test only control group design. Sample of 21 Wistar rats that have met the inclusion and exclusion criteria,adapted for 7 days. After a period of adaptation,Wistar rats were divided by simple random sampling into 3 groups. K is a control group without borax given orally. Borax P1 given orally 300 mg / kg /day ( 100 mg / cc / day ) and P2 borax was given orally 600 mg / kg / day ( 200 mg / cc / day).Results : The results of the Kruskal - Wallis test for kidney macroscopic found no significant differences between the 3 groups ( p = 0.083 ) and then proceed Mann Whitney Post Hoc Test for kidney weight was not found significant differences in the K - P1 ( p = 0.482 ), obtained difference K - P2 significant ( p = 0.041 ),and found no significant difference P1 - P2 ( p = 0.085 ). Kruskal - Wallis test results for the microscopic kidney obtained significant differences between the 3 groups ( p = 0.000 ).Conclusion : Delivery of oral doses of borax stratified for 4 weeks followed 2 weeks without exposure to borax no macroscopic changes ( kidney weight ) in Wistar rats as well as a change in the microscopic ( histopathological ) Wistar rat kidney. Changes seen in the form of lumen narrowing,and loss of brush border protein cast ( lumen contains ).